SPEECH ACT IN ROBERT ZEMECKIS MOVIE SCREENPLAY “FORREST GUMP” - Putra, Dimas Dwi; Sopha, Diana (PHILOLOGY Journal of English Language and Literature, 2024)
In this thesis entitled Speech Act in Robert Zemeckis Movie Screenplay "Forrest Gump", the researcher will examine the use of speech acts used in the movie. This research used a descriptive qualitative method. This movie screenplay was chosen because there are many speech acts that occur in the dialogue. The theory used in data analysis uses pragmatic theory. The aim of this research is to analyze dialogues that contain speech acts, then classify them based on the type of speech act, namely locutionary acts and illocutionary acts. After analyzing the data, there are three types of locutionary acts, namely declarative, imperative and interrogative. Then there are five types of illocutionary acts, namely representative, directive, commissive, expressive and declarative which are found in the movie screenplay of this movie.